Peningkatan Stres Siswa dengan Sistem Pembelajaran Fullday School - Vivi Jumini; Suhermi; Wa Ode Sri Asnaniar (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Education is an important process to increase children's potential. The problem currently faced in the world of education is that teaching staff strive to create efficient teaching methods a limited duration and hope that students are able to achieve commensurate learning outcomes. One of the innovations implemented to achieve maximum duration is implementing a full day school system in schools. However, this system requires physical and mental preparation. Because if they are not prepared, students will certainly become bored and even experience stress. This research aims to determine the description of students' stress levels using the full day school learning system at SMA Negeri 3 Makassar. The research design used is descriptive quantitative with a crosssectional approach. Sample determination was carried out using a purposive sampling technique with a sample size of 79 students in accordance with the inclusion and exclusion criteria. The research instrument is the DASS-45 questionnaire which was modified and distributed via WhatsApp in the form of a Goggle Form. The results of the research showed that the description of the stress level of students using the full day school learning system at SMA Negeri 3 Makassar was in the moderate stress level category as many as 22 students (27.8%) and the statement most frequently responded by students was the statement